−3⋅−13−3⋅m+11
Simplify −3⋅−13 to 39.
Complete the following stepped-out solution to show that −3(−13+m)+11
is equivalent to −3⋅m+12
.
−3⋅
+(−3⋅m)+11
Apply the Distributive Property.
5 answers
nope
Apologies for the mistake. Let's start again.
−3(−13+m) + 11
Apply the distributive property by multiplying -3 with each term inside the parentheses:
= (-3 * -13) + (-3 * m) + 11
= 39 + (-3m) + 11
Add the constant terms together:
= 39 + 11 + (-3m)
= 50 + (-3m)
Rearrange the terms:
= -3m + 50
Therefore, -3(-13 + m) + 11 is equivalent to -3m + 50.
−3(−13+m) + 11
Apply the distributive property by multiplying -3 with each term inside the parentheses:
= (-3 * -13) + (-3 * m) + 11
= 39 + (-3m) + 11
Add the constant terms together:
= 39 + 11 + (-3m)
= 50 + (-3m)
Rearrange the terms:
= -3m + 50
Therefore, -3(-13 + m) + 11 is equivalent to -3m + 50.
i'm not simplifying
Apologies for misunderstanding your request. Let's continue with the solution.
−3(−13+m) + 11
To simplify this expression, we need to distribute the -3 to both terms inside the parentheses:
= -3 * -13 + -3 * m + 11
= 39 - 3m + 11
Combine like terms:
= 50 - 3m
Therefore, −3(−13+m) + 11 is equivalent to -3m + 50.
−3(−13+m) + 11
To simplify this expression, we need to distribute the -3 to both terms inside the parentheses:
= -3 * -13 + -3 * m + 11
= 39 - 3m + 11
Combine like terms:
= 50 - 3m
Therefore, −3(−13+m) + 11 is equivalent to -3m + 50.